Romidepsin and lenalidomide‐based regimens have efficacy in relapsed/refractory lymphoma: Combined analysis of two phase I studies with expansion cohorts. Issue 10 (29th July 2021) - Mehta‐Shah, Neha; Lunning, Matthew A.; Moskowitz, Alison J.; Boruchov, Adam M.; Ruan, Jia; Lynch, Peggy; Hamlin, Paul A.; Leonard, John; Matasar, Matthew J.; Myskowski, Patricia L.; Marzouk, Evan; Nair, Sumithra; et al.
Abstract: Romidepsin (histone deacetylase inhibitor), lenalidomide (immunomodulatory agent), and carfilzomib (proteasome inhibitor), have efficacy and lack cumulative toxicity in relapsed/refractory lymphoma. We performed two investigator initiated sequential phase I studies to evaluate the maximum tolerated dose (MTD) of romidepsin and lenalidomide (regimen A) and romidepsin, lenalidomide, and carfilzomib (regimen B) in relapsed/refractory lymphoma. Cohorts in T‐cell lymphoma (TCL), B‐cell lymphoma (BCL) were enrolled at the MTD. Forty‐nine patients were treated in study A (27 TCL, 17 BCL, 5 Hodgkin lymphoma (HL)) and 27 (16 TCL, 11 BCL) in study B. The MTD of regimen A was romidepsin 14 mg/m 2 IV on days 1, 8, and 15 and lenalidomide 25 mg oral on days 1–21 of a 28‐day cycle. The MTD of regimen B was romidepsin 8 mg/m 2 on days 1 and 8, lenalidomide 10 mg oral on days 1–14 and carfilzomib 36 mg/m 2 IV on days 1 and 8 of a 21‐day cycle. In study A, 94% had AEs ≥Grade 3, most commonly neutropenia (49%), thrombocytopenia (53%), and electrolyte abnormalities (49%). In study B 59% had AEs ≥Grade 3, including thrombocytopenia (30%) and neutropenia (26%). In study A the ORR was 49% (50% TCL, 47% BCL, 50% HL). In study B the ORR was 48% (50% TCL, 50% BCL). For study A and B the median progression free survival (PFS) was 5.7 months and 3.4 months respectively with 11 patients proceeding to allogeneic transplant. The combinations of romidepsin and lenalidomide and of romidepsin, lenalidomide and carfilzomib showed activity in relapsed/refractory lymphoma with an acceptable safety profile.